Estudo da corrosão atmosférica dos aços patináveis e aço carbono expostos em site de uma termelétrica no Ceará - Santos, Valéria Sousa dos (2020)
Weathering steels are alloys with anti-corrosion properties, that develop over time a compact andlowporous oxide layer, whichcandecreasesubstratedegradation. Still, the material is not free from corrosion, and the complex processand subject to the action ofweathering and contaminants in the atmosphere. In an attempt to understand the action of contaminants compared to the weathering steels (USI-SAC 350M, experimental steel with extra resistance to the marine atmospheric corrosionand USI-SAC 300), carbonsteel (ASTM A36), searches corrosion were made to characterize, classify, and map the corrosivity in the thermoelectric plant, located on the coast of Ceará, using a methodology based on the implementation of six atmospheric corrosion stations (ECAs). For this, these materials were evaluated monthly for mass loss. Additionally, the corrosion products were characterized by x-ray diffraction, x-ray fluorescence and scanning electronmicroscopy. The values found are results for the corrosivity classification of the studied atmosphere and helped in the understanding of the mass loss analysis of the studied materials. It was found that for carbonsteel, the environment is framed at C5 (145 μm /yr), and the US-ISAC 350M and. USI-SAC 300M weathering steels had average corrosion rates of 18 μm / yr and 14 μm / yr, respectively, indicating classification C2. This result showed na equivalent performance of the two investigated weathering steels and higher corrosion resistance than carbono steel.